Ответ:
[tex](\frac{a}{b}+\frac{c}{d})(\frac{e}{f}) =\frac{ae}{bf}+ \frac{ce}{df}[/tex]
Объяснение:
[tex](\frac{a}{b}+\frac{c}{d})(\frac{e}{f}) =\frac{a}{b}\cdot \frac{e}{f}+ \frac{c}{d}\cdot\frac{e}{f} =\frac{a\cdot e}{b\cdot f}+ \frac{c\cdot e}{d\cdot f} =\frac{ae}{bf}+ \frac{ce}{df}[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex](\frac{a}{b}+\frac{c}{d})(\frac{e}{f}) =\frac{ae}{bf}+ \frac{ce}{df}[/tex]
Объяснение:
[tex](\frac{a}{b}+\frac{c}{d})(\frac{e}{f}) =\frac{a}{b}\cdot \frac{e}{f}+ \frac{c}{d}\cdot\frac{e}{f} =\frac{a\cdot e}{b\cdot f}+ \frac{c\cdot e}{d\cdot f} =\frac{ae}{bf}+ \frac{ce}{df}[/tex]